2022
DOI: 10.1186/s12870-022-03689-4
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan nanoparticles improve physiological and biochemical responses of Salvia abrotanoides (Kar.) under drought stress

Abstract: Background The use of organic nanoparticles to improve drought resistance and water demand characteristics in plants seems to be a promising eco-friendly strategy for water resource management in arid and semi-arid areas. This study aimed to investigate the effect of chitosan nanoparticles (CNPs) (0, 30, 60 and 90 ppm) on some physiological, biochemical, and anatomical responses of Salvia abrotanoides under multiple irrigation regimes (30% (severe), 50% (medium) and 100% (control) field capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 123 publications
1
12
0
Order By: Relevance
“…The CS applications are known to interfere positively with a myriad of complex networks including cellular signaling, transcription processes, ionic and water transport, cell redox homeostasis and metabolic activities in germinating seeds. All such CS-mediated physiological and biochemical positive correlations enhance seedling development by minimizing the toxic effects of salt stress [ 79 ]. Further, the polyphenols of GTE serve as the first line of defense due to their direct antioxidant role to maintain cellular redox homeostasis for well-regulated metabolic activities for germination and seedling development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CS applications are known to interfere positively with a myriad of complex networks including cellular signaling, transcription processes, ionic and water transport, cell redox homeostasis and metabolic activities in germinating seeds. All such CS-mediated physiological and biochemical positive correlations enhance seedling development by minimizing the toxic effects of salt stress [ 79 ]. Further, the polyphenols of GTE serve as the first line of defense due to their direct antioxidant role to maintain cellular redox homeostasis for well-regulated metabolic activities for germination and seedling development.…”
Section: Discussionmentioning
confidence: 99%
“…Considering priming as a facile approach and the high efficiency of nanomaterials, we hypothesized that a biodegradable and nontoxic biopolymer and natural phytochemicals could be exploited as sustainable resources to prepare nanocomposite as an environment-friendly priming agent. Chitosan (CS) is a biodegradable biopolymer, a heterogeneous and cationic polysaccharide that regulates immune signaling, carbon and nitrogen metabolism in plants thus stimulate plant growth and elicit stress resistance [ 28 30 ]. Green tea is enriched with polyphenols predominantly catechins which possess a broad spectrum of biological activities including high antioxidant potential [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, NPs mitigate drought-induced ROS through the aggregation of osmolytes, which results in enhanced osmotic adaptation and crop water balance ( Alabdallah et al., 2021 ). Furthermore, NPs increase the photosynthetic activity, upregulate aquaporins, modify the intracellular water metabolism, accumulates compatible solutes, maintain intracellular ion homeostasis, increase stomatal density, and reduce water loss from leaves through stomatal closure due to fostered ABA accumulation ( Attaran Dowom et al., 2022 ; Kandhol et al., 2022 ).…”
Section: Nps For Plant Protection Against Abiotic Stressmentioning
confidence: 99%
“…Moreover, CH has a unique bioactive property that can prevent serious injury to plants under stressful conditions by triggering the mechanisms of plant defense (Mohammadi et al 2021). Previous research has shown the use of CH as an antiperspirant (Attaran et al 2022). In this respect, (Mphande et al 2020) divided antiperspirants into three main groups: (A) physical antiperspirants forming a thin layer on the stomata to prevent water evaporation; (B) reflective antiperspirants that improve the light reflectivity of leaf surfaces, reducing leaf temperature; (C) physiological antiperspirants containing certain compounds influencing the guard cells around the stomata and inducing plants to close it.…”
Section: Introductionmentioning
confidence: 99%